Analisis Volume Sedimen Berdasarkan Hasil Pengukuran Dengan Echosounder Dalam Waduk Bili-bili Kabupaten Gowa - Elisa Trinofri Sanjaya; Melly Lukman; Benyamin Tanan (Paulus Civil Engineering Journal, 2020)
The Bili-Bili Reservoir, Gowa Regency, South Sulawesi Province is a multipurpose reservoir built-in 1994. The Bili-Bili Reservoir was built with the aim of the management and utilization of water resources, as well as to prevent flooding in the rainy season. During its development, there has been a decline in the use of the reservoir service function due to the presence of sediment in the reservoir. From the results of measurements in 2017, at an elevation of +99.5 m (normal water level), the reservoir capacity decreased from 347.81 million m3 to 239.76 million m3 over 20 years due to a large amount of sediment in the Bili-Bili Reservoir. The total volume of sediment from 1997 - 2017 was 108,050 million m3. If this continues, the remaining useful life of the Bili-Bili Reservoir will not be effective. The purpose of this study is to determine the volume of sediment in the Bili-Bili Reservoir, Gowa Regency, South Sulawesi Province in 2019. This research is a field measurement using an Echosounder and secondary data collection in the form of a contour map of the Bili-Bili Reservoir. 1997. From the results of Echosounder measurements, a basic contour map of the Bili-Bili Reservoir in 2019 was made with the 1997 reservoir map, and cross-sections were made as to the basis for calculating the volume of sediment. Based on the results of research and calculations, the total volume of sediment in the Bili-Bili reservoir from 1997 to 2019 was 110,371 million m3 and in 2017 the total volume of sediment was only 108,050 million m³. The total sediment rate in 2017 to 2019 is 2,321 million m³.